Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru - Sonedi Sonedi; Tutut Sholihah; Dihasbi Dihasbi (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to determine the leadership of the head of the madrasah at Palangkaraya MTsN 1 in improving the performance of the Palangkaraya 1 MTsN Model teacher. The approach used in this study is a qualitative approach with a case study method. Data collection uses observation, interview and documentation study techniques with emphasis on informant data sources, namely: Head of madrasah, teachers, and students to strengthen the validity of the data obtained. Based on the results of the study that the head of the madrasa in Palangka Raya 1 MTsN Model has a type of democratic leadership and is very instrumental in carrying out its leadership as educator, manager, administrator, supervisor, leader, and motivator in improving performance in planning, implementing and evaluating classroom learning, and always empower human resources in decision making. Teacher performance in MTsN 1 This model, has carried out an effective week analysis, prota, prosem, availability of media syllabus, list of values, and attendance list of students. The performance of subject teachers in learning planning is in a very good category. The teacher has been disciplined in carrying out his duties as an Educator. In its implementation to improve teacher performance, the headmaster of the madrasah has included the teachers every time there is training in accordance with the field of study. Besides that, the headmaster also gives awards to the teacher, although not in the form of material but in the form of mental support and praise for continuing to develop the potential he has.